PENERAPAN INTERNET OF THINGS PADA PROTOTYPE SMART HOME MENGGUNAKAN POLA SUARA DENGAN MIKROKONTROLER NODEMCU - M. Abu Jihad Plaza R; Hanum Maghfiro Risky Ningtias (Sienna, 2023)
This article discusses the implementation of Internet of Things (IoT) on a prototype smart home using voice patterns with NodeMCU microcontroller. The system is designed to control electronic devices and objects in the house through voice commands. The system uses Nest Mini as a voice capture media, NodeMCU as the center of the system, and lamps and fans as smart home devices. The system works when the user gives voice commands to turn on and off the devices. The system is controlled through the internet and can be accessed through a smartphone. The study shows that the prototype smart homework according to the intended purpose.